2017
DOI: 10.1590/0103-6440201701365
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Remineralizing Potential and Antimicrobial Activity of a Cariostatic Agent with Silver Nanoparticles

Abstract: Cariostatic treatment has been shown to successfully arrest caries. However, it blackens the carious tooth structure. This study evaluated the effects of an experimental cariostatic agent with silver nanoparticles (Ag-Nano) using microhardness (MH) and microbiological tests. The cariostatic agents tested were: Saforide®, Cariestop®, Ancarie® and Ag-Nano. Sixty-six samples from deciduous enamel were submitted to initial (after pH cycling to obtain initial caries-like lesion) and final (after cariostatic applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 18 publications
(44 reference statements)
2
37
1
3
Order By: Relevance
“…However, it has shown adverse effects, such as causing ulcerations and staining in oral mucosa [ 64 ] that are painful due to accidental contact with the solution [ 20 , 65 ], which may disappear within 48 hours [ 21 , 65 ] and the black staining of carious tissue [ 65 – 67 ] due to the oxidation process of the ionic silver contained in its formulation [ 4 , 68 ]; however, as previously demonstrated, the use of a cariostatic agent with silver nanoparticles does not cause darkening in demineralized teeth [ 46 – 48 , 51 ]. Besides, practically all studies have demonstrated the anticariogenic and remineralizing effect of silver nanoparticles alone [ 45 ] and in combination with various components, being superior to conventional treatments [ 48 51 ] such as silver diamine fluoride when applied once a year, with the advantage of not staining black dental tissue, the reason being they do not form oxides when in contact with oxygen in the environment, no metallic taste, and lower cost compared to SDF [ 4 , 51 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has shown adverse effects, such as causing ulcerations and staining in oral mucosa [ 64 ] that are painful due to accidental contact with the solution [ 20 , 65 ], which may disappear within 48 hours [ 21 , 65 ] and the black staining of carious tissue [ 65 – 67 ] due to the oxidation process of the ionic silver contained in its formulation [ 4 , 68 ]; however, as previously demonstrated, the use of a cariostatic agent with silver nanoparticles does not cause darkening in demineralized teeth [ 46 – 48 , 51 ]. Besides, practically all studies have demonstrated the anticariogenic and remineralizing effect of silver nanoparticles alone [ 45 ] and in combination with various components, being superior to conventional treatments [ 48 51 ] such as silver diamine fluoride when applied once a year, with the advantage of not staining black dental tissue, the reason being they do not form oxides when in contact with oxygen in the environment, no metallic taste, and lower cost compared to SDF [ 4 , 51 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Also, in the agar diffusion tests, a greater inhibition of S. mutans , Enterococcus faecalis , and Escherichia coli by Saforide® was observed than by Ancarie® and Ag-Nano. However, the MIC Ag-Nano inhibited the growth of microorganisms at a concentration lower than the other agents, remineralizing also the enamel of deciduous teeth with initial like-caries lesion [ 45 ].…”
Section: Agnps Formulations In Caries Prevention and Arrestmentioning
confidence: 99%
“…These reports used 6 different human oral cells (3 kinds of squamous cell cancer cell lines, pulpal cells, gingival fibroblasts, and periodontal ligament cells) and found severe toxicity in them (most of the cells were dead at 0.039 mM) (García-Contreras et al 2013). Another study reported the inhibition of bacterial growth (Scarpelli et al 2017). In summary, the substantial toxicity of Saforide is an issue in clinical dental practice, but f-GO nanocomposites are expected to solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…The demineralizing solution utilized was USP grade citric acid (1 wt%), and the storage solution prior to the antimicrobial action, as well as their anti-adherent effects on oral biofilms [10]. AgNPs have also been shown in multiple studies to increase microhardness of HAP and prevent demineralization at high risk sites, such as around orthodontic brackets and composites [2,3,11]. However, plant based AgNPs have not been tested for their remineralization capacity in vitro.…”
Section: Optimizing Prevention Strategiesmentioning
confidence: 99%
“…This is due to their antimicrobial, antiviral, and antifungal properties [1]. Additionally, multiple studies have shown that AgNPs can not only prevent demineralization, but can also remineralize tooth structure [2,3]. It was the purpose of this study to evaluate whether or not a novel rinse containing plant based AgNPs could remineralize severely demineralized enamel.…”
Section: Introductionmentioning
confidence: 99%